Inhibition of porcine reproductive and respiratory syndrome virus replication by rifampicin in vitro - Wei, Ruiping; Li, Lu; Chen, Haifan; Wang, Xiaoying; Chen, Yaosheng; Liu, Xiaohong (Frontiers in Veterinary Science, 2024)
Porcine reproductive and respiratory syndrome virus (PRRSV) continues to cause significant economic losses to the global swine industry, yet effective prevention and control measures remain elusive. The development of novel antivirals is thus urgently needed. Rifampicin (RFP), a semisynthetic derivative of rifamycin, has been previously reported to inhibit the replication of certain mammalian DNA viruses as well as RNA viruses. In this study, we unveil RFP as a potent inhibitor of PRRSV both in Marc-145 cells (half-maximal inhibitory concentration 61.26 μM) and porcine alveolar macrophages (half-maximal inhibitory concentration 53.09 μM). The inhibitory effect of RFP occurred during viral replication rather than binding, internalization and release. We also demonstrated that RFP inhibits PRRSV proteins production in the early stage of infection, without inhibiting host protein synthesis.Moreover, RFP effectively restricted porcine epidemic diarrhea virus (PEDV) and porcine enteric alphacoronavirus (PEAV) infection in Vero cells. In summary, these findings indicate the promising potential of RFP as a therapeutic agent for PRRSV, PEDV and PEAV infection in pig farms.